Controlling the photochemical reaction of an azastilbene derivative in water using a water-soluble pillar[6]arene. Issue 36 (1st September 2017) - Xia, Danyu; Wang, Pi; Shi, Bingbing
Abstract : A host–guest system in water based on a water-soluble pillar[6]arene and an azastilbene derivative, ( E )-4, 4′-dimethyl-4, 4′-diazoniastilbene diiodide, has been constructed. Then this water-soluble pillar[6]arene was successfully used to control the photohydration of the azastilbene derivative in water as a "protective agent". Abstract : Photochemistry plays an important role in our lives. It has also been a common tool in the laboratory to construct complicated systems from small molecules. Supramolecular chemistry provides an opportunity to solve some of the problems in controlling photochemical reactions via non-covalent interactions. By using confining media and weak interactions between the medium and the reactant molecule, the excited state behavior of molecules has been successfully manipulated. Pillararenes, a new class of macrocyclic hosts, have rarely been used in the field of photochemical investigations, such as the controlling of photo-induced reactions. Herein, we explore a synthetic macrocyclic host, a water-soluble pillar[6]arene, as a controlling tool to manipulate the photo-induced reactions (hydration) in water. A host–guest system in water based on a water-soluble pillar[6]arene and an azastilbene derivative, ( E )-4, 4′-dimethyl-4, 4′-diazoniastilbene diiodide, has been constructed. Then this water-soluble pillar[6]arene was successfully employed to control the photohydration of the azastilbene derivative in water as a "protective agent".